1985
DOI: 10.1002/1520-6629(198501)13:1<31::aid-jcop2290130105>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

“They call you a dole bludger”: Some experiences of unemployment

Abstract: The responses of 100 unemployed people to an open‐ended question about their current experiences were content analyzed to yield assessments of their current experiences. The experiential elements of Set 1 were uncertainty, anxiety, depression, anger (directly and indirectly expressed), good feelings, helplessness, competence, and alienation. Set 2 consisted of an expansion of the anxiety element, and Set 3, of the alienation element. When their scores were compared with those of a relatively low stress group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
3
0
5
Order By: Relevance
“…Las emociones que surgen ante una situación como el desempleo suelen tener una dimensión afectiva negativa, producen una activación del individuo orientada al aumento de la ansiedad, la depresión o el estrés y su afrontamiento emocional puede manifestarse de diversas maneras, tal como se expone a continuación. Por ejemplo, en una investigación cualitativa sobre el patrón de respuesta emocional en un grupo de personas desempleadas las emociones más frecuentes fueron la depresión, la ira, la impotencia, la tristeza, el aislamiento social y el sentimiento de culpa, todas con una dimensión afectiva negativa (Vine, 1985). Además, en este estudio se encontraron diferencias entre los grupos de edad de los participantes: las personas más jóvenes expresaron más sentimientos de rabia y ansiedad que las personas de más edad (Vine, 1985).…”
Section: Reacciones Emocionales Ante La Situación De Desempleounclassified
See 1 more Smart Citation
“…Las emociones que surgen ante una situación como el desempleo suelen tener una dimensión afectiva negativa, producen una activación del individuo orientada al aumento de la ansiedad, la depresión o el estrés y su afrontamiento emocional puede manifestarse de diversas maneras, tal como se expone a continuación. Por ejemplo, en una investigación cualitativa sobre el patrón de respuesta emocional en un grupo de personas desempleadas las emociones más frecuentes fueron la depresión, la ira, la impotencia, la tristeza, el aislamiento social y el sentimiento de culpa, todas con una dimensión afectiva negativa (Vine, 1985). Además, en este estudio se encontraron diferencias entre los grupos de edad de los participantes: las personas más jóvenes expresaron más sentimientos de rabia y ansiedad que las personas de más edad (Vine, 1985).…”
Section: Reacciones Emocionales Ante La Situación De Desempleounclassified
“…Por ejemplo, en una investigación cualitativa sobre el patrón de respuesta emocional en un grupo de personas desempleadas las emociones más frecuentes fueron la depresión, la ira, la impotencia, la tristeza, el aislamiento social y el sentimiento de culpa, todas con una dimensión afectiva negativa (Vine, 1985). Además, en este estudio se encontraron diferencias entre los grupos de edad de los participantes: las personas más jóvenes expresaron más sentimientos de rabia y ansiedad que las personas de más edad (Vine, 1985).…”
Section: Reacciones Emocionales Ante La Situación De Desempleounclassified
“…dependents and rental obligations, expressed feelings of alienation, anxiety, and anger. 16 Fry, in a study of stress perceptions in Vietnamese refugees who were 25-35 years old, found that sporadic employment and uncertainty of employment were the primary reasons for stress experienced. He also suggested that his Vietnamese subjects were similar to other depressed individuals in that they tended to over-emphasize the negative effects such as job insecurity and social isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Some theorists conceptualize unemployment as a trauma or major loss event that induces psychological reactions similar to bereavement or terminal illness (Middlebrook & Clarke, 1991; Winegardner, Simonetti, & Nikodym, 1984). Documented negative reactions include increased depression, anger, worry, and threats to identity, self-concept, and self-esteem (Goldsmith, Veum, & Darity, 1996; Keefe, 1984; Madonia, 1983; Viney, 1985). Other theorists emphasize the loss of control and learned helplessness that unemployment can evoke, leading to motivational and performance deficits (Baum, Fleming, & Reddy, 1986; Goldsmith & Darity, 1992).…”
mentioning
confidence: 99%